THE ASSESSMENT OF LOWER THIRD MOLAR ANGULATION CHANGES DURING ORTHODONTIC TREATMENT USING ORTHOPANTOMOGRAPHY - Loredana Golovcencu; Georgeta Zegan; Daniela Anistoroaei; Iulia Catalina Saveanu (Romanian Dental Association for Education, 2019)
Third lower molar prognostic of eruption or impaction can be assessed by different measurements on radiographic exams. Aim of the study. To find out if the lower third molar angulation with the mandibular and the occlusal plane at the beginning of the orthodontic treatment is a reliable measurement on orthopantomograms for its prognostic of eruption or impaction. Material and methods. On the orthopantomograms taken at the beginning and at the end of the treatment of 70 teenagers orthodontic patients with 128 lower third molars we measured the angle formed between the long axis of the mandibular molar and the mandibular plane and the occlusal plane, respectively. 47 of our patients undergone non extraction orthodontic treatment, and 23 had removal of lower first premolars for orthodontic reasons. the measurements were done separately for each group. Results. For both measurements there were differences in the lower third molar angulation during treatment with or without extractions, but there are no correlative changes in lower third molar status in order to be able to consider any prognostic value at the beginning at the orthodontic treatment regarding the future evolution of this tooth. Conclusions. Lower third molar angulation with the mandibular plane or with the occlusal plane changes unpredictable during orthodontic treatment and has little or no influence from first premolar removal.